PENERAPAN MODEL PEMBELAJARAN KOOPORATIF TIPE INDEX CARD MATCH DAPAT MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS IV SDN. 003 TELUK BANO II KEC. PEKAITAN KAB. ROKAN HILIR - Misran Misran; Mahmud Alpusari; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is driven by the fact that the students' science learning outcomes appear low and there are still many students who have not reached the KKM. Of the 20 students only 10 students (50%) reached KKM. And 10 students (50%). This research is a classroom action research conducted in Class V SDN 026 Padang Mutung Kampar District. The research instrument consisted of Learning Aid Tool used in this research is guided by Education Unit Level Curriculum (SBC), which is known as learning tool Curriculum 2006 consists of syllabus, lesson plan, student worksheet and observation sheet. The first meeting for the first cycle of teacher activity with the average teacher activity observed in the second cycle increased compared to the first cycle. At my first meeting the average processing teacher activity averaged 54% in sufficient category, at the second meeting the average of teacher activity increased to 66% also in the Good category. At the third meeting of the second cycle the average activity of 75% of teachers with good category and fourth meeting with an average of 87% activity in the category of Very Good. The first meeting of the first cycle averaged 41% of the student activity with sufficient category, at the second meeting the average activity increased to 66% in both categories. At the third meeting the second cycle averaged 83% of the student activity in very good category and the fourth meeting increased compared to the previous meeting with an average of 91% student activity with very good category. Student learning outcomes after preliminary student data of more than KKM only 10 people (50%) after the first cycle increased up to 12 people (60%) after the second cycle increased to 16 people (80%) Similarly, average grade point average students acquired classically at the beginning and after only 61.5 cycles I increased an average of 68 and in the second cycle will increase to 73. This means that the classical value obtained by students above the KKM has been determined.Keywords: Keywords: Model Cooporative Learning Type Index Card Match, Learning Outcomes Civics